SSA 04-1 SIMILARITIES AND DIFFERENCES IN LATIN AMERICAN GUIDELINES FROM OTHERS. (September 2016) - Ramirez, Agustin
Abstract : The presentation will focus on the different guidelines we have actually in hands (JNCHT 8, ESH / ESC, ISH) and compare them to the last Latin-American Society of Hypertension Guidelines to be published in this year. In this way, we will focus our attention in the socio-economic problem of the different countries in LA and the differences we have included in our Guidelines due to the actual needs in LA. Additionally we will specially mention the special populations from LA like andineans, people living over 500m from sea level, and the different black populations that are different from those described in North America. Relating treatment the need to use generic forms of drugs related to the economic difficulties to access to original drugs will also be discussed. Finally the need for further studies relating epidemiology, prevalence of hypertension and the morbi-mortality related will be presented.